Complexities of expressive word learning over time. - McGregor KK; Sheng L; Ball T (Language, Speech & Hearing Services in Schools, 2007)
PURPOSE: The purpose of this study was to examine semantic and lexical aspects of word learning over time. METHOD: Thirty-four 8-year-olds participated in vocabulary lessons for 2 weeks. Frequency of exposure and informativeness of semantic context were manipulated. A definition task assessed semantic learning and a naming task assessed lexical learning. RESULTS: Semantic and lexical knowledge accrued over time and were maintained after a 1-month interval. Higher frequency of exposure had an immediate effect on semantic learning and a more gradual effect on lexical learning. Frequency of exposure coupled with informative context promoted semantic learning. CLINICAL IMPLICATIONS: Speech-language pathologists should be mindful of the richness of the learning context and the redundancy of massed and distributed exposures. Learning at the semantic and lexical levels can dissociate so both should be addressed.